Rights to be Deducted from the Capital of the Decedent’s Inheritance and those Apportioned from One Third of the Estate - Haj, Mohammed Saleh Mohammed (Journal of Islamic Sciences, 2023)
The study addressed what should be deducted from the deceased’s estate, Huququ’llah (the Rights of Allah Almighty) that should be deducted from the estate and from one third of the estate and what should be deducted from the estate for other financial dispositions. The study aimed to clarify what should be deducted from the estate (Tarikah) and from one third of the estate, and the jurists’ views about that. The study also aimed to explain the choices of the Yemeni Personal Status Code regarding the issues presented and to collect the issues that are related to each other in one research so that they will be clear. To achieve that, the researcher adopted three approaches: the descriptive approach by which he mentioned the issues presented in the research, editing the aspects of agreement and disagreement, if any, and attributing the sayings to the doctrines and the jurists who said them. The second approach is the inductive approach by which the researcher mentioned the sayings of the four doctrines including some sayings of the scholars and other doctrines especially those that have an actual existence nowadays. The third approach is the analytical approach by which the researcher mentioned some jurisprudential sayings about an issue, analyzing them, comparing them with the Yemeni Code and then selecting the appropriate opinion for the issue. The researcher has reached some of the findings, of which the most important is that deducting the rights of Allah from the estate such as Zakat, vows, alms and expiations achieves social justice and reduces class inequality. The researcher also reached that both the followers of Imam Al-Shafi’e and the followers of Imam Zaid agree that deducting the Rights of Allah (Zakat) from the capital is a must because it is a worship related to money.